SIMILARITIES BETWEEN TURKISH AND UZBEK (Academia Science Repository, 2023)
The oldest alphabet of Turks as known Gokturk alphabet. We can see this alphabet on the monuments of Orhon, Yenisev and Talas which are presently in Mongolia. These monuments were erected in 8th century. After the waning of the Gokturk state, the Uighurs produced a new alphabet named Uighur. By the time Turks adopt Arabic, Krill and Latin alphabets depends on religious or political reason. Turkish and Uzbek are two languages that belong to the Turkic language family. Both languages share similar linguistic features due to their common historical and cultural background. In this article, we will explore the similarities between Turkish and Uzbek in terms of their phonetics, vocabulary, grammar, and syntax.